2016
DOI: 10.1080/08897077.2015.1035841
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Multicomponent Screening, Brief Intervention, and Referral to Treatment (SBIRT) Training Curriculum on a Medical Residency Program

Abstract: Background Substance-related disorders are a growing problem in the United States. The patient-provider setting can serve as a crucial environment to detect and prevent at-risk substance use. Screening, brief intervention, and referral to treatment (SBIRT) is an integrated approach to deliver early intervention and treatment services for persons who have or are at-risk for substance related disorders. SBIRT training components can include online modules, in-person instruction, practical experience, and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Only 4 studies (5%) set a priori skill benchmarks for their SBIRT training curriculum. 51,54,76,84 There were no studies in this review that set benchmarks specifically for MI proficiency. No studies measured SBIRT or MI skill longitudinally or connected trainee SBIRT skill with patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Only 4 studies (5%) set a priori skill benchmarks for their SBIRT training curriculum. 51,54,76,84 There were no studies in this review that set benchmarks specifically for MI proficiency. No studies measured SBIRT or MI skill longitudinally or connected trainee SBIRT skill with patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17] Feasibility studies from the early phases of these projects determined that infusing SBIRT curriculum into existing training programs was indeed possible. [13][14][15][18][19][20][21][22][23][24] The progress of developing and implementing curricula that yielded changes in resident attitudes and behaviors has been substantial. Residents not only reported satisfaction with training, 13-14, 17, 25 they also demonstrated improvements in knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…This has been shown in other studies where primary care physicians received a short training course on mental health management, and training resulted in a positive change in attitudes (Al-Khathami et al , 2003; Mitchel et al , 2016). A study by Kanu et al (2016) found even short modules of SBIRT training delivered to medical students quickly lead to acquisition of SBIRT skills in practice. Thus residency educators who have limited time or resources may utilize as few as one mode of training to disseminate skills among healthcare providers.…”
Section: Discussionmentioning
confidence: 99%